गणित, इयत्ता सहावी - (:unkn) unknown (Maharashtra State Bureau of Textbook Production & Curriculum Research, 2011)
The book is a Marathi medium Mathematic texbook for class-6.
Mathematics, Class 6
Keywords: Marathi; गणित; इयत्ता सहावी; Mathematics; Class 6; Mathematics; Marathi; Marathi